THE EFFECTIVENESS OF CIRC METHOD AND COMIC-STRIP MEDIA TO ENGLISH WRITING ABILITY OF THE MECHANICAL ENGINEERING STUDENTS - Fenny Thresia (Jurnal Pedagogy, 2017)
University students have to be able towrite in English,the ability is not only expected to English educations’ students but also for all students in University. The purpose of this study is to determine the effectiveness of the comic-strip media in improving mechanical engineering students in writing ability. In this research, the research will be focus on the procedure text.This research applied quasi-experimental “pre-test post-test design”. It is conducted at the Muhammadiyah University of Metro in academic Year 2015/2016. The Population involved in this study is mechanical engineering students which consist of 60 students. The researcher took all the population as the sample of this study;30 students as experimental class and 30students as control class. The variables of this study are (1) CIRC Method with comic-strip media as independent variables, (2) Ability to write as the dependent variable. The instrument used in this study is the writing test. To analyze the data, researchers uses ttestformula.The results showed the value of ttestTTable 3.57 and 2.00 (criterion 1) and 2.66 (criterion 2). From these results it can be concluded that the CIRC method through comic strips can improve writing ability in mechanical engineering students.